Enhancement of Quality and Milled Rice Yield Recovery Through The Improvement of Polishing Process and Configuration. Issue 1 (1st May 2022) - Rachmat, R; Rahayu, E; Darniadi, S; Hadipernata, M
Abstract: In general, small to medium scale rice mills in Indonesia produced low rice yield and relatively inefficient operational cost. The objective of study was to improve the performance of the rice milling unit (RMU) through revitalizing the process and milling configuration. The research was conducted in 2019 on medium-scale rice mills located in the Laboratory of Rice Quality and Cereal Postharvest (LRQCP), in Karawang. The research method was designed by empirical data analysis from the change of polishing methods from the abrasive-friction became the abrasive - abrasive polishing system, followed by tempering tank before entering into the third process with friction mist-polishing system. The observed parameters were physical rice quality, and performance of the milling process, included the economic analyses of Net B/C ratio. Physical analysis of paddy and milled rice quality was carried out at the LRQCP, in Karawang. The rice quality evaluation was conducted according to the Regulation of Agricultural Minister no.31, 2017. The research results showed after revitalization the rice recovery of Ciherang variety increased (0.72%) as well as Inpari 32 variety became 0.91% respectively. the milled rice appearances became cleaner and glossy. The economic analyses of Net B/C ratio matched the economic viability (> 1).